Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1073/pnas.94.26.14725
|View full text |Cite
|
Sign up to set email alerts
|

In vivo NMR and MRI using injection delivery of laser-polarized xenon

Abstract: Because xenon NMR is highly sensitive to the local environment, laser-polarized xenon could be a unique probe of living tissues. Realization of clinical and medical science applications beyond lung airspace imaging requires methods of efficient delivery of laser-polarized xenon to tissues, because of the short spin-lattice relaxation times and relatively low concentrations of xenon attainable in the body. Preliminary results from the application of a polarized xenon injection technique for in vivo 129 Xe NMR͞M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…[234,235] and Ref. The above model predicts that laser-polarized xenon could be delivered to certain tissues more efficiently by injection than by respiration [236]. For example, it was suggested that by assuming reasonable values for the parameters in Eq.…”
Section: A Model Of Injection Delivery Of Laser-polarized Xenonmentioning
confidence: 99%
See 2 more Smart Citations
“…[234,235] and Ref. The above model predicts that laser-polarized xenon could be delivered to certain tissues more efficiently by injection than by respiration [236]. For example, it was suggested that by assuming reasonable values for the parameters in Eq.…”
Section: A Model Of Injection Delivery Of Laser-polarized Xenonmentioning
confidence: 99%
“…The feasibility of using injectable carriers of laser-polarized xenon to perform in vim NMR and MRI was demonstrated in living laboratory rats [236]. In each experiment of this work, ml cc of a saturated polarized xenon solution was prepared according to the procedure described in Section 8.…”
Section: In Vavo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…8.12). The surface coil was used to monitor 12gXeNMR signals from the rat's liver region, permitting the wash-in/washout dynamics of the xenon in (PPm) Figure 8.12: In vivo 129XeNMR spectrum obtained by summing the 7th through 12th acquisitions following the intravenous injection of a laser-polarized xenon/Intralipid solution [236]. The signals were detected with a surface coil placed over the rat's liver region.…”
Section: Injection Delivery Of Laser-polarized Gases 228mentioning
confidence: 99%
“…For these investigations, the gas is either dissolved in the blood via inhalation or predissolved in a biologically compatible liquid that is then injected. Xenon is 10 -100 times more soluble than helium in most of the previously investigated carriers (blood, saline, intralipid, and perfluorocarbon emulsions) (7)(8)(9)(10)(11)(12). In addition, 129 Xe experiences a wide range of chemical shifts in different solvents, which should be advantageous for both functional imaging and perfusion studies (13).…”
mentioning
confidence: 99%